Symbiotic Agency in Swapnil Smriti’s Poem ‘Story of Kabhra Tree on Round Chautari’ - Dhungel, Nabaraj; Thapa, Kalpana (Molung Educational Frontier, 2026)
This article examines how Swapnil Smriti’s poem “Story of Elephant Fig Tree (Kabhra) on Round Platform (Chautari)” employs the Kabhra-Pipal binary to explore plant-human agency. The contrasting symbols of the Kabhra and Pipal trees reflect the socio-political, cultural, religious, and cognitive dimensions of society. The study highlights how Smriti uses these trees to initiate a resistance and a renarrativization movement. The Kabhra tree represents the history, culture, nature, love, communal life, faith, and seasonal markers of the Kirat community in eastern Nepal, while the Pipal tree symbolizes the imperialist, oppressive, and expansionist culture, religion, and politics associated with King Prithvi Narayan Shah, who prioritized territorial expansion over cultural and emotional integration. The paper demonstrates how Smriti boldly challenges marginalized identities, striving to restore the Kirat community’s original ethnic identity and advocating for freedom and equity through plant narratives. It argues that the binary sparks a counter-establishment movement, fostering environmental-indigenous citizenship and planting seeds of counter-hegemonic consciousness among culturally displaced groups, particularly the Kirat. To support the claim, the analysis draws on Matthew Hall’s concept of plant agency and Ferdinand de Saussure’s theory of binary opposition. This research offers valuable insights for global movements seeking to revive the politico-cultural identities of ethnic communities through plant-human agency.